The Effect Of Work Environment And Workload On Employee Work Productivity Of Pt. Horti Jaya Lestari Cabang Dokan - Purba, Rindiany; Siregar, Onan Marakali (Cattleya Darmaya Fortuna, 2023)
The existence of instability of production at PT. Horti Jaya Lestari Dokan shows a decrease in employee productivity. Factors that can increase work productivity, such as work environment and workload. This study aims to analyze the effect of the work environment and workload on the work productivity of PT. Horti Jaya Lestari Dokan. The effect of work environment and workload will be tested partially and simultaneously on work productivity. The form of this research is quantitative research with an associative approach. The population is all employees of PT. Horti Jaya Lestari Dokan has as many as 71 respondents. The data collection technique is primary data obtained through direct questionnaire distribution and secondary data obtained through books, journals and related to this research. The analytical methods used are validity tests, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The work environment and workload have a significant effect on work productivity.